Periodistas y ciudadanía ante la mixtura de información y opinión en los mensajes periodísticos. Investigación de campo en la Comunidad de Madrid (2007-2009) - Herrera Damas, Susana; Maciá Barber, Carlos (Estudios sobre el Mensaje Periodístico, 2010)
Principles, standards, recommendations and codes of journalism ethics set the rigid separation between information and opinion in informative and interpretative genres. Although most part of the professionals practicing in Madrid share this postulate, a significant percentage shows permissive inclusion of author’s perspective in some messages, such as features, chronicles, informativos de autor1 and in the “lightest” thematic areas (culture, entertainment, sport, or gossip, for instance). On the contrary, respondents reject political and economic content when telling the news. This perception is similar to the one showed by citizens in Madrid who, however appreciate the informativos de autor.
Keywords: Journalistic Ethics; Journalistic Genres; Information; Opinion; Spain